O gosto do D.O.M.: a construção da experiência estética e estésica na gastronomia brasileira - Neiva, Rodrigo César Severino (2023)
Until the end of the 1990s, the existing gastronomic restaurants in Brazil were typical representatives of European cuisine, led by foreign chefs, following creations and ways of serving from their countries of origin. National ingredients were used either to replace ingredients that were not found here or to give a sense of exoticism to an international cuisine production. In 1999, the restaurant D.O.M., led by Alex Atala, opens the path for a Brazilian development of gastronomy. This was the first restaurant to receive two stars from the Michelin Guide and, in 2012, it reached fourth position on the list of the 50 best restaurants in the world. The objective of this research is to analyze the construction of the aesthetic experience of Brazilian gastronomy. For the development of this work, six visits to the restaurant were carried out, between August 2018 and June 2022, which allowed us to analyze the dishes created by the chef, understood as a significant enunciation. The initial hypothesis of this work is that the physical space of the restaurant, its decoration, the reservation platform, the texts of the menu, the ambient music, the utensils and the service of the hall, in addition to the dishes developed for the tasting menu, are elements that, articulated, are capable of provoking a feeling of euphoria to the tasting subject. Through analyzes in the light of discursive semiotics and studies on taste and aesthesia, we verify the syntagmatic choices of Atala, the subject of the enunciation, and the contribution of each of these elements to the development of his paradigm of Brazilian gastronomy, a gastronomy grounded in indigenous cuisine, which has Brazilian ingredients as its protagonist and which presents intertextual relations with Italian and Japanese cuisines. Beyond identifying a definitive model, our contribution was to understand the aesthetic experience proposed and the paths opened by D.O.M., seeking to point out ways for other constructions in Brazilian gastronomy